Early childhood caries and associated determinants: a cross‐sectional study on Italian preschool children. (9th October 2013) - Congiu, Giovanna; Campus, Guglielmo; Sale, Silvana; Spano, Giovanni; Cagetti, Maria Grazia; Lugliè, Pietrina Francesca
Abstract Objectives This study evaluates the influence of several determinants on the presence of early childhood caries (ECC) in preschool children living in northern Sardinia, Italy. These determinants include the educational level and occupational status of the parents as a proxy for the socioeconomical level (SES) and behavioral factors (dietary and oral hygiene). Methods An observational cross‐sectional study was designed with a dental examination and a standardized questionnaire. Five hundred forty‐four subjects (260 girls and 284 boys) were enrolled and categorized into two age groups: 359 children were aged 18‐47 months and 185 children were aged 48‐60 months. Results The total caries prevalence was 15.99%. Caries risk increased with lower parents' educational level (P = 0.01), increased number of siblings (P < 0.01), the use of bottle feeding (P = 0.02), and the use of a sweetened baby's pacifier at night (P = 0.01). In robust multivariate analysis, a high parental educational level played a protective role on the presence of caries lesion [odds ratio (OR) = 0.51, 95% confidence interval (CI) 0.34‐0.78]; the mother's being employed had a positive statistically significant association with the child having decayed, missing, filled tooth surfaces = 0 (OR = 0.64, 95% CI 0.23‐0.97). The presence of more than one sibling in the family was associated with caries (OR = 1.70, 95% CI 1.20‐2.40). Conclusion ECC prevalence evaluated was similar to other western countries, and SES and behavioral habits influence the development of ECC.